SLOT ANTENNA DEVICE FOR MICROWAVE RANGE WITH 4-PORT SIGNAL FEEDING - POLITANSKY, RUSLAN; PLOSHCHYK, ANNA; CHESANOVSKYI, IVAN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The relevance of this research is determined by the need for high-performance antenna devices that can be used in microwave and millimeter-wave frequency ranges. These devices are characterized by a high degree of miniaturization compared to other frequency ranges, as well as a complex dependence on various parameters such as geometric dimensions, substrate thickness, and signal feeding methods. The prototype selected is a classic slot antenna, modified by reducing its size to a surface area of 4×4 cm² and increasing the number of signal feeding ports to four. The study involved investigating the frequency dependence of the reflection coefficient of the input signal relative to the dielectric substrate thickness in the range of 3 to 10 mm. Additionally, the spatial radiation pattern of the antenna was examined. Based on the obtained results, resonance frequencies in the range of 5 to 15 GHz were identified, where the reflection coefficient of the input signal does not exceed -10 dB, and the antenna gain coefficient ranges from 2.72 to 6.35. It was also found that there is no significant interaction between the individual signal feeding ports. The obtained characteristics were compared with other devices operating in the microwave and millimeter-wave ranges. The loss coefficient associated with signal reflection at resonance frequencies is comparable to the results presented in the review section. The spatial radiation pattern of the investigated antenna (quad-slot antenna) features narrow directed beams, providing a high antenna gain coefficient, whereas many devices described in the literature exhibit either nearly isotropic or semi-isotropic patterns. The research was conducted using the student version of the ANSOFT HFSS software. The developments can be applied to advanced telecommunication systems designed to meet high-speed and stability requirements, such as the Internet of Things (IoT) and cyber-physical systems. The results of this research hold potential for practical implementation in future communication systems, offering scientific value in terms of high-frequency antenna device evaluation methods.